ProSPective evaluation of the dIagnostic accuracy of siNe spiN non-contrast flatdEtectoR CT (FDCT) for the detection of intracranial hemorrhage in stroke patients - Protocol of a non-inferiority comparison to multi detector CT - Marios Psychogios; Alex Brehm; Nitin Goyal; Grégoire Boulouis; Jan-Karl Burkhardt; Shakeel A. Chowdhry; Donald Frei; Jan Gralla; Johannes Kaesmacher; Ryan T. Kellogg; Christopher P. Kellner; Demetrius K. Lopes; et al. (PLoS ONE, 2025)
Rationale Whether syngo DynaCT Sine Spin non-contrast flat detector CT (FDCT) imaging is sufficient to rule out intracranial hemorrhage in suspected acute stroke patients is unknown. Aim To determine if syngo DynaCT Sine Spin non-contrast FDCT imaging is non-inferior to conventional multidetector CT (MDCT) imaging for the detection and exclusion of intracranial hemorrhages in suspected acute stroke patients. Sample size To enroll 252 participants in three buckets (126 ischemic stroke patients, 126 hemorrhagic stroke patients (including 14 patients with an isolated infratentorial hemorrhage). Methods and design A multicenter, international, prospective, cross-sectional, endpoint assessor blinded, non-inferiority trial. Outcomes The primary outcome is the occurrence of an intracranial hemorrhage (yes versus no). This will be used to calculate the sensitivity and specificity of FDCT imaging for the detection of intracranial hemorrhages. All FDCT images will be rated by six independent raters in a blinded imaging core-lab. The rating of the MDCT images will be deemed as ground-truth. FDCT imaging will be deemed non-inferior if the lower bound of the 95%-Confidence Interval of the sensitivity and specificity is above 95%. Discussion This trial will inform physicians whether syngo DynaCT Sine Spin non-contrast FDCT imaging can reliably exclude intracranial hemorrhages in patients with suspected acute stroke. Trial registration ClinicalTrials.gov NCT05458908